Quality intrapartum care expectations and experiences of women in sub-Saharan African Low and Low Middle-Income Countries: a qualitative meta-synthesis - Salma A. E. Ahmed; Abela Mahimbo; Angela Dawson (BMC, 2023)
Abstract Background Woman-centred maternity care is respectful and responsive to women's needs, values, and preferences. Women's views and expectations regarding the quality of health services during pregnancy and childbirth vary across settings. Despite the need for context-relevant evidence, to our knowledge, no reviews focus on what women in sub-Saharan African Low and Low Middle-Income Countries (LLMICs) regard as quality intrapartum care that can inform quality guidelines in countries. Methods We undertook a qualitative meta-synthesis using a framework synthesis to identify the experiences and expectations of women in sub-Saharan African LLMICs with quality intrapartum care. Following a priori protocol, we searched eight databases for primary articles using keywords. We used Covidence to collate citations, remove duplicates, and screen articles using a priori set inclusion and exclusion criteria. Two authors independently screened first the title and abstracts, and the full texts of the papers. Using a data extraction excel sheet, we extracted first-order and second-order constructs relevant to review objectives. The WHO framework for a positive childbirth experience underpinned data analysis. Results Of the 7197 identified citations, 30 articles were included in this review. Women's needs during the intrapartum period resonate with what women want globally, however, priorities regarding the components of quality care for women and the urgency to intervene differed in this context given the socio-cultural norms and available resources. Women received sub-quality intrapartum care and global standards for woman-centred care were often compromised. They were mistreated verbally and physically. Women experienced poor communication with their care providers and non-consensual care and were rarely involved in decisions concerning their care. Women were denied the companion of choice due to cultural and structural factors. Conclusion To improve care seeking and satisfaction with health services, woman-centred care is necessary for a positive childbirth experience. Women must be meaningfully engaged in the design of health services, accountability frameworks, and evaluation of maternal services. Research is needed to set minimum indicators for woman-centred outcomes for low-resource settings along with actionable strategies to enhance the quality of maternity care based on women's needs and preferences.